Together We Will : Experimental Evidence on Female Voting Behavior in Pakistan - Giné, Xavier; Mansuri, Ghazala (2012)
In many emerging democracies women are less likely to vote than men and, when they do vote, are more likely to follow the wishes of household males. The authors assess the impact of a voter awareness campaign on female turnout and candidate choice. Geographic clusters within villages were randomly assigned to treatment or control, and within treated clusters, some households were left untreated. Compared with women in control clusters, both treated and untreated women in treated clusters are 12 percentage points more likely to vote, and are also more likely to exercise independence in candidate choice, indicating large spillovers. Data from polling stations suggest that treating 10 women increased turnout by about 9 votes, resulting in a cost per vote of US$ 2.3. Finally, a 10 percent increase in the share of treated women at the polling station led to a 6 percent decrease in the share of votes of the winning party.